An exact spectral-dynamic stiffness method for free flexural vibration analysis of orthotropic composite plate assemblies – Part II: Applications. (15th November 2015) - Liu, X.; Banerjee, J.R.
Abstract: An exact spectral-dynamic stiffness method (S-DSM) for free vibration analysis of composite plates and plate assemblies has been proposed in Part I of this two-part paper. The main purpose of this Part II paper is twofold: (i) To validate and demonstrate the superiority of the proposed S-DSM and (ii) To establish exact benchmark solutions for free vibration of composite plate-like structures. The S-DSM is applied to a number of problems covering orthotropic composite plates and plate assemblies. It is demonstrated that the S-DSM gives exact solutions with high computational efficiency within low as well as high frequency ranges. The applications are completely general and the new development can handle complex plate shapes with any boundary conditions.